Phylogenetic Comparison and Splicing Analysis of the U1 snRNP-specific Protein U1C in Eukaryotes - Zhang, Kai-Lu; Zhou, Jian-Li; Yang, Jing-Fang; Zhao, Yu-Zhen; Das, Debatosh; Hao, Ge-Fei; Wu, Caie; Zhang, Jianhua; Zhu, Fu-Yuan; Chen, Mo-Xian; Zhou, Shao-Ming (Frontiers in Molecular Biosciences, 2021)
As a pivotal regulator of 5’ splice site recognition, the U1 small nuclear ribonucleoprotein (U1 snRNP)-specific protein C (U1C) regulates pre-mRNA splicing by interacting with other components of U1 snRNP complex. Previous studies have shown that U1 snRNP and its components are linked to variety of diseases including cancer. However, phylogenetic relationship and expression profiles of U1C have not been studied systematically. To this end, we identified a total of 110 animal U1C genes and compared to the homologs from yeast and plants. Bioinformatics analysis shows that the structure and function of U1C proteins is relatively conserved, and is found in multiple copies in few members of U1C genes family. Furthermore, expression pattern showed that U1Cs have potential role in cancer progression and human development. In summary, our study presents a comprehensive overview of animal U1C gene family, which can provide fundamental data and potential cues for further research in deciphering the molecular function of this splicing regulator.